2022
DOI: 10.1186/s40359-022-00846-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of loving-kindness meditation on employees’ mindfulness, affect, altruism and knowledge hiding

Abstract: Background This study investigated the effects of the loving-kindness meditation (LKM) on employees’ mindfulness, affect, altruism and knowledge hiding. Methods In total, 100 employees were recruited from a knowledge-based enterprise in China and randomly divided into the LKM training group (n = 50) and the control group (n = 50). The LKM training group underwent LKM training for 8 weeks, while the control group did not. Seven main variables (mindf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 95 publications
0
17
0
Order By: Relevance
“…Mindfulness is not only a way of emotion regulation, but also a kind of emotion regulation ability. Previous studies have shown that mindfulness is closely related to emotion regulation ( Lutz et al, 2014 ; McLaughlin et al, 2019 ; Liu et al, 2022b ), in which there is a spiraling process between mindfulness and positive emotions, that is, by improving individual mindfulness, people with positive emotions will generate more positive emotions in the future, and the increase of positive emotions predicts more mindfulness ( Du et al, 2019 ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Mindfulness is not only a way of emotion regulation, but also a kind of emotion regulation ability. Previous studies have shown that mindfulness is closely related to emotion regulation ( Lutz et al, 2014 ; McLaughlin et al, 2019 ; Liu et al, 2022b ), in which there is a spiraling process between mindfulness and positive emotions, that is, by improving individual mindfulness, people with positive emotions will generate more positive emotions in the future, and the increase of positive emotions predicts more mindfulness ( Du et al, 2019 ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Fifth, although flow is often considered an optimal experience that helps individuals regulate their emotions and improve their wellbeing (Chen et al, 2022b ), the role of flow in inducing problematic SVA use suggests its downside, which has been understudied in prior research. This reminds us to revisit flow in relation to mindfulness, a state of paying full attention to the present (Bishop et al, 2004 ; Regan et al, 2020 ; Liu et al, 2022a ) and keeping a non-judgmental awareness of one's internal experiences (Baer et al, 2006 ; Kabat-Zinn, 2015 ). Overall, there are two approaches to understand flow and mindfulness (Chiou et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Covid-19 pandemic has induced adolescents' increased engagement on social media for multiple activities: work (Liu et al, 2022e), education (Hsu et al, 2021), socialization (Liu et al, 2021), entertainment (Chen et al, 2022a,b), etc., which Frontiers in Psychology frontiersin.org contrast to previous explorations of hardware technology adoption and parent-child relationship quality as causal factors influencing parental intervention environments, an online family environment ("whether they are friends online" and "parents' knowledge of their children's use") was introduced based on a parent-child interaction perspective to fit the new scenario of social media use.…”
Section: Discussionmentioning
confidence: 99%
“…The Covid-19 pandemic has induced adolescents’ increased engagement on social media for multiple activities: work ( Liu et al, 2022e ), education ( Hsu et al, 2021 ), socialization (Liu et al, 2021), entertainment ( Chen et al, 2022a , b ), etc., which may influence parental intervention strategies. Our study focused on parental intervention in the post-pandemic era.…”
Section: Discussionmentioning
confidence: 99%